Decreased whole-blood global DNA methylation is related to serum hormones in anorexia nervosa adolescents. (May 2014) - Tremolizzo, L.; Conti, E.; Bomba, M.; Uccellini, O.; Rossi, M.S.; Marfone, M.; Corbetta, F.; Santarone, M.E.; Raggi, M.E.; Neri, F.; Ferrarese, C.; Nacinovich, R.
Abstract: Objectives. The one-carbon metabolism, also known as methionine-homocysteine cycle, governs the dynamics of DNA methylation, epigenetically regulating gene expression, and has been reported altered in anorexia nervosa (AN) adult patients. The aim of this study consisted in assessing whole-blood DNA methylation in adolescent AN patients, assessing its significance in relationship to clinical and hormonal variables. Methods. Whole-blood global DNA methylation was measured as incorporation of [ 3 H]dCTP following Hpa II cut in 32 adolescent females affected by restrictive type AN and compared to 13 healthy controls. Homocysteine, vitamin B12 and folate plasma levels were assessed as well as fasting plasma levels of leptin and steroid hormones. Clinical variables, including severity and associate states and traits, were assessed by means of the EDI-3, CDI and STAI-Y scales. Results. We confirm that whole-blood global DNA methylation is modestly albeit significantly reduced in AN adolescents with respect to controls, correlating with plasma leptin and steroid hormone levels. Conversely, clinical traits did not correlate with the outcome variable. Conclusions. A better definition of the epigenetic dysregulation underlying AN pathology or vulnerability might lead to develop useful markers for diagnosis, prognostic classification and tailored therapeutic interventions in these vulnerable patients since the earliest phases of their disease.